Estomias gastrointestinais em crianças e adolescentes: experiência da família - Zacarin, Clara Ferraz Lazarini (Universidade Federal de São Carlos, 2014)
Gastrointestinal stoma are openings in the skin that enable the extracorporeal communication of the stomach or intestine to gain access to the body when there is need to divert traffic from the normal supply or disposal. The ostomy of the gastrointestinal tract in children are part of malignancies, benign, inflammatory, congenital or traumatic treatments. Having a stoma in childhood and/or adolescence makes physical and psychological changes, because of organic immaturity, and affects the body integrity, social interaction and quality of life. Caring for a child with ostomy brings impacts to the family and generates hard demand of permanent and specific care. This study aimed to understand the experience of families with children and adolescents who have gastrointestinal stomas. Qualitative approach was used, in light of Symbolic Interactionism as a theoretical framework and the methodological framework of Narrative Analysis. For data collection, were used conducted interviews by guiding questions and during the same interviews were made the construction of the genogram and ecomap to characterize the family . Interviews were conducted with 16 families, 12 with children and 4 with adolescents with gastrointestinal stoma using outpatient nutritional or ostomy services. In six families the children had intestinal stomas and ten had gastrostomy. The analysis process has resulted in 6 themes and categories: 1. Impact of unexpected illness (Facing the stoma as a consequence / Senso undergone a many procedures); 2 Acceptation of the ostomy (having difficulty accepting the stoma / Leaving reach the limit); 3 - Changes in family life (Adapting to the managements of the devices / Leaving aside the social life); 4 - Helplessness on the walk (having superficial support / Living with prejudice); 5 - Benefits of ostomy; 6 - Search the social reintegration (Seeing the power social interaction / Waiting for reversal). The results of this study allowed us to understand that the family of the child or adolescent with gastrointestinal stoma goes through a process of progressive experience and acceptance of the condition of the child, which starts with the impact of the diagnosis of unexpected illness. Feelings like fear and insecurity are evidenced by distancing and denial of the need to make the stoma. After the acceptance and learning period, the family notice the clinical and health improves of the child, but goes through prejudice situations and alienation of the extended family, difficulties in maintaining employment, and maternal burden in the care of the ostomy´s son. The support network is reduced and there is only strengthened ties among members of the nuclear family. Even before the difficulties the family has a positive view of the stoma, but crave reenter the child/adolescente in society through the stoma reversal in the case of intestinal and through oral feeding, at the gastrostomy, even when it is permanent. The results of this study make it possible to broaden our understanding of the experience, which in turn improves the care of these families, Being a breakthrough for the field of nursing.
Keywords: Enfermagem familiar; Pediatria; Estomaterapia; Ostomizados; Jovens; Estomas cirúrgicos; Gastrostomia; Família; Criança; Surgical stomas; Gastrostomy; Family; Child; Adolescent; CIENCIAS DA SAUDE::ENFERMAGEM